2022
DOI: 10.1088/2515-7620/ac5718
|View full text |Cite
|
Sign up to set email alerts
|

The role of trust in public acceptability of energy projects: Integrity versus competence

Abstract: Public acceptability of energy projects depends on people’s trust in agents responsible for those projects. We examined to what extent different dimensions of trust, notably integrity- and competence-based trust, are associated with public acceptability of real ongoing energy projects associated with acute risks and other consequences. A series of questionnaire studies in the Netherlands revealed that both integrity- and competence-based trust were positively associated with public acceptability of natural gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The results are coherent with those of previous studies – integrity trust has a positive correlation with the perceived quality of interactions (Liu et al , 2022). The results are partially consistent with Cheung and Lai (2022), who find that integrity trust is an important motivator for the quality of interactions during both stages, but this study finds that integrity trust is only significant during the pre-engagement stage.…”
Section: Discussionsupporting
confidence: 91%
“…The results are coherent with those of previous studies – integrity trust has a positive correlation with the perceived quality of interactions (Liu et al , 2022). The results are partially consistent with Cheung and Lai (2022), who find that integrity trust is an important motivator for the quality of interactions during both stages, but this study finds that integrity trust is only significant during the pre-engagement stage.…”
Section: Discussionsupporting
confidence: 91%
“…Literature suggests that people commonly assess institutions at least in terms of their expertise and knowledge (i.e., competence-based trust) and on whether their intentions seem honest and taking the public interest into account (integrity-based trust) (Terwel et al 2009, Perlaviciute and Steg 2014, Liu et al 2020a, Kitt et al 2021, Siegrist 2021, Liu et al 2022. These dimensions tap into the two (universal) dimensions people typically use to evaluate social information (e.g., other people, social groups, objects): competence and warmth, respectively (Fiske et al 2007).…”
Section: Competence and Integrity-based Trustmentioning
confidence: 99%
“…Both competence-based and integrity-based trust have been found to be associated with higher public acceptability of energy policies and projects (Bronfman et al 2015). Yet, correlational and experimental research has shown that integrity-based trust is more strongly associated with the public acceptability of energy projects than competence-based trust (Liu et al 2020a(Liu et al , 2022. For example, higher integrity-based trust in a hypothetical energy company tasked with the implementation of a renewable energy project led to higher public acceptability of such a project, no matter the level of competence-based trust people had in the energy company.…”
Section: Competence and Integrity-based Trustmentioning
confidence: 99%
“…Although numerous other categorizations exist in the broad literature on social trust, existing studies suggests that trust can be seen as a two-dimensional structure consisting of competence and integrity (Eckerd et al, 2021). In addition, both stronger competence-based and integrity-based trust are related to higher public acceptance in energy projects, carbon dioxide capture and storage project and climate engineering (Kitt et al, 2021;Liu et al, 2020Liu et al, , 2022.…”
Section: Social Environmentmentioning
confidence: 99%